2011
DOI: 10.1111/j.1600-0447.2011.01787.x
|View full text |Cite
|
Sign up to set email alerts
|

The association between social phobia, social anxiety cognitions and paranoid symptoms

Abstract: The present study showed that paranoid symptoms and social phobia share similarities in cognitive profile and inhibited temperament. Avoidance appears to be important in the development of social phobia, whereas cannabis use and traumatic experiences may drive paranoid thinking in vulnerable individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 116 publications
(236 reference statements)
2
33
1
Order By: Relevance
“…For instance, it has been suggested that individuals with paranoid thoughts and/or persecutory delusions can demonstrate a personalising bias (tendency to infer blame of negative outcomes to individuals rather than situations) (Couture, 2006). Alternatively negative interpretations of ambiguous events and catastrophic interpretations of negative events have been reported previously in individuals with schizophrenia (Schutters et al, 2012). These tendencies require consideration for how interactions and environments are managed in physical activity contexts.…”
Section: The Vulnerability Of Individuals With Schizophrenia To the Ementioning
confidence: 99%
“…For instance, it has been suggested that individuals with paranoid thoughts and/or persecutory delusions can demonstrate a personalising bias (tendency to infer blame of negative outcomes to individuals rather than situations) (Couture, 2006). Alternatively negative interpretations of ambiguous events and catastrophic interpretations of negative events have been reported previously in individuals with schizophrenia (Schutters et al, 2012). These tendencies require consideration for how interactions and environments are managed in physical activity contexts.…”
Section: The Vulnerability Of Individuals With Schizophrenia To the Ementioning
confidence: 99%
“…Conversely, a Swiss-based cohort reported that young adults with psychotic-like experiences were significantly more likely to later develop common mental disorders, such as anxiety disorders and MDD 13. A German community-based study found an association between social phobia, social anxiety and DLE,14 while a US primary-care-based sample reported that those who reported psychotic-like experiences were more likely to have generalised anxiety disorders and panic disorders 15…”
Section: Introductionmentioning
confidence: 99%
“…Given these similarities, comparing social anxiety and paranoia can clarify the boundaries of paranoia and its place within clinical disorders. A moderate to strong relation of anxiety—both social and general—with paranoia is reported [23], [24], [25]. Studies using non-clinical samples report that paranoid thoughts often build upon relatively common interpersonal worries and anxiety [5], and studies of patients with schizophrenia and spectrum disorders suggest that anxiety may predict the development of paranoia [26], [27].…”
Section: Introductionmentioning
confidence: 99%